Energy transfer assisted frequency upconversion in Ho 3+ doped fluoroindate glass - Rakov, N.; MacIel, G. S.; Araújo, Cid B. de; Messaddeq, Younes [UNESP] (AIP Publishing, 2002)
Experimental results are reported which show a strong evidence of energy transfer between Ho 3+ ions in a fluoroindate glass excited by a pulsed laser operating at 640 nm. We identified the origin of the blue and green upconverted fluorescence observed as being due to a Ho 3+-Ho 3+ pair interaction process. The dynamics of the fluorescence revealed the pathways involved in the energy transfer assisted upconversion process. © 2002 American Institute of Physics.
Keywords: Fluoroindate glass; Frequency up-conversion; Pair interactions; Up-conversion process; Fluorescence; Glass; Energy transfer